"I'm running my depression:" Self-management of depression in neoliberal Australia - Brijnath, Bianca; Antoniades, J. (Pergamon Press, 2016)
The current study examines how the neoliberal imperative to self-manage has been taken up by patients, focusing specifically on Indian-Australians and Anglo-Australians living with depression in Australia. We use Nikolas Rose's work on governmentality and neoliberalism to theorise our study and begin by explicating the links between self-management, neoliberalism and the Australian mental health system. Using qualitative methods, comprising 58 in-depth interviews, conducted between May 2012 and May 2013, we argue that participants practices of self-management included reduced use of healthcare services, self-medication and self-labour. Such practices occurred over time, informed by unsatisfactory interactions with the health system, participants confidence in their own agency, and capacity to craft therapeutic strategies. We argue that as patients absorbed and enacted neoliberal norms, a disconnect was created between the policy rhetoric of self-management, its operationalisation in the health system and patient understandings and practices of self-management. Such a disconnect, in turn, fosters conditions for risky health practices and poor health outcomes.